(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
An article about the protest letter sent by Bohemian nobles to the Council of Constance after they sentenced two Church reformists to death. The author begins by describing the circumstances of the document’s creation and then explains how the document came to Scotland. He also notes that there were at least four copies of this letter but suggests that the copy in Edinburgh might be the ‘principal’ copy. The Edinburgh copy of the protest is then quoted in full. Some coins commemorating the event were also exhibited at this meeting.